The Effect of Blended Learning of Student Teams Achievement Division (STAD) and Jigsaw Towards Higher-Order Thinking Skills - Sandi Kurniawan (EDUTEC : Journal of Education And Technology, 2021)
Higher-order thinking skills is an ability that all vocational high school students should have because vocational high school graduates are required to have the good soft skill and hard skill. The reality was their HOTS ability was low, as stated by several explanations from researchers and strengthened by the observation in vocational high school. This research aimed to find the students' learning activity through blended learning of Student Teams Achievement Division (STAD) model and jigsaw model, and their influence on the HOTS. This research was quantitative research using the quasi-experiment method of nonequivalent control group design with research subjects of 50 students that were chosen using simple random sampling. The data was collected using test instruments in multiple choices and descriptions and non-test tool in the form of observation sheets. The data then were analyzed with t-test sample independent test. The results showed that the usage of STAD and jigsaw blended learning made students more active and energized in following the learning activities. The direct learning model made students inactive and not excited during learning activities. Also, the blended learning of STAD and jigsaw had significant influence compared to the direct learning model on higher-order thinking skills.